2005
DOI: 10.1210/jc.2004-1062
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Interferon-γ-Inducible Chemokine-10/CXC Chemokine Ligand-10 in Autoimmune Primary Adrenal Insufficiency andin VitroExpression in Human Adrenal Cells Primary Cultures after Stimulation with Proinflammatory Cytokines

Abstract: Chemokines are a large family of cytokines involved in the pathogenesis of inflammatory and autoimmune diseases. Among CXC chemokines, CXC chemokine ligand 10 (CXCL10) has been identified to play an important role in several endocrinological autoimmune diseases, such as Hashimoto's thyroiditis, Graves' disease, and type 1 diabetes mellitus. Although the mechanisms leading to glandular autoimmune process may be at least in part shared by different endocrine organs, the role of CXCL10 in autoimmune adrenal insuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 37 publications
4
41
0
2
Order By: Relevance
“…In particular, the synergy between the two cytokines is essential in potentiating inflammatory and Th1 immune responses promoted by IFNg. To date, previous studies reported that CXCL10 secretion is triggered only by IFNg in different resident cell types (Rotondi et al 2005, Antonelli et al 2006d, while in microvascular endothelium TNFa has been reported to upregulate cytokines other than CXCL10 (Sana et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the synergy between the two cytokines is essential in potentiating inflammatory and Th1 immune responses promoted by IFNg. To date, previous studies reported that CXCL10 secretion is triggered only by IFNg in different resident cell types (Rotondi et al 2005, Antonelli et al 2006d, while in microvascular endothelium TNFa has been reported to upregulate cytokines other than CXCL10 (Sana et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of corticosteroids on cytokine-induced CXCL10 secretions was studied in primary cell cultures of human zona fasciculata cells (hZFC) from normal adrenal glands (211). CXCL10 was undetectable basally, whereas its secretion was significantly induced in hZFC by stimulation with IFN-␥ or IFN-␥ plus TNF-␣ (Fig.…”
Section: B Corticosteroids In Vitro Inhibit Cxcl10 Production Inducementioning
confidence: 99%
“…The absence of a gender-related effect in AAD, either isolated or occurring within APS-2, suggested that autoimmune adrenalitis by itself was responsible for the high circulating levels of CXCL10. In the same study (Rotondi et al, 2005), it was also shown that release of CXCL10 by primary cell cultures of human zona fasciculata cells (hZFC) was undetectable basally, but significantly induced by stimulation with IFN- or IFN- plus TNF-, while stimulation of hZFC with TNF- alone was not able to induce chemokine secretion. Interestingly, increasing concentrations of hydrocortisone progressively and significantly inhibited IFN--induced and IFN--plus TNF--induced CXCL10 secretion (Rotondi et al, 2005).…”
Section: Pathophysiology Of Aadmentioning
confidence: 86%
“…In the same study (Rotondi et al, 2005), it was also shown that release of CXCL10 by primary cell cultures of human zona fasciculata cells (hZFC) was undetectable basally, but significantly induced by stimulation with IFN- or IFN- plus TNF-, while stimulation of hZFC with TNF- alone was not able to induce chemokine secretion. Interestingly, increasing concentrations of hydrocortisone progressively and significantly inhibited IFN--induced and IFN--plus TNF--induced CXCL10 secretion (Rotondi et al, 2005). The inhibitory effect of glucocorticoids on chemokine production is in line with their antiinflammatory and immunosuppressive actions.…”
Section: Pathophysiology Of Aadmentioning
confidence: 86%
See 1 more Smart Citation